A Comparison on Hyponymy and Cultural Symbolism of Six Color Words between Chinese Language and Bahasa Indonesia - Rahayu, Kristina Indah Setyo (Bina Nusantara University, 2014)
Color words originate from natural world. In general different languages have similar patterns of color hypernymy. Nevertheless, when it comes to color hyponymy, it is not the case. Specific color hyponyms have emerged because different countries have different cultures. Besides, color words are also rich in cultural symbolism. In other words, same colors in different countries have different cultural symbolisms. This paper analyzed six color words (red, white, yellow, blue, green, and black) between Chinese language and bahasa Indonesia to find similarities and differences both in hyponymy and in culture symbolism.